Multisystem inflammatory syndrome drug treatment in countries with different income profiles: a scoping review - Nagem Lopes, Luis Phillipe; da Cunha, Lidiane Gomes; Silva, Alice Ramos Oliveira; Land, Marcelo Gerardin Poirot; Fonseca, Adriana Rodrigues; Lopes, Luciane Cruz; Lima, Elisangela Costa (Frontiers in Pharmacology, 2023)
The purpose of this study was to map and describe the studies that have investigated therapeutic alternatives for the management of paediatric multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19. Considering the origin of the studies performed (low-, middle-and high-income countries), a systematic scoping review was conducted with primary studies that reported the use of medications for the treatment of patients with MIS-C. Sources: The searches were performed in MEDLINE, Embase, Lilacs, Epistemonikos, CINAHL and CENTRAL, in the grey literature (theses and dissertations from CAPES, ProQuest, and PROSPERO) and in clinical trial databases until May 2022. The selection and extraction of studies were performed independently by two reviewers. Summary of the findings: A total of 173 studies were included, most of which were published as case reports or series. No randomized controlled clinical trials (RCTs) were identified. The investigated drugs were immunoglobulins, glucocorticoids, monoclonal antibodies, anticoagulants, and antiplatelet agents. Conclusions: The dosages, when reported, were heterogeneous among the studies. The ethnicity and comorbidity of the participants were poorly reported. Monoclonal antibodies, drugs with higher costs, were mostly described in studies of high-income countries.